2021
DOI: 10.3748/wjg.v27.i46.7909
|View full text |Cite
|
Sign up to set email alerts
|

Enteric nervous system and inflammatory bowel diseases: Correlated impacts and therapeutic approaches through the P2X7 receptor

Abstract: The enteric nervous system (ENS) consists of thousands of small ganglia arranged in the submucosal and myenteric plexuses, which can be negatively affected by Crohn’s disease and ulcerative colitis - inflammatory bowel diseases (IBDs). IBDs are complex and multifactorial disorders characterized by chronic and recurrent inflammation of the intestine, and the symptoms of IBDs may include abdominal pain, diarrhea, rectal bleeding, and weight loss. The P2X7 receptor has become a promising therapeutic target for IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 172 publications
1
5
0
1
Order By: Relevance
“…The quantitative analysis identified a reduction in the number of nNOS-ir, ChAT-ir, and GPR41-ir neurons in the Colitis group when compared to the Sham group. These results corroborate data from the literature that document the reduction of enteric neurons in IBD protocols [8][9][10]51]. In this study, after 7 days of acid injection, neuronal reduction was observed.…”
Section: Discussionsupporting
confidence: 92%
“…The quantitative analysis identified a reduction in the number of nNOS-ir, ChAT-ir, and GPR41-ir neurons in the Colitis group when compared to the Sham group. These results corroborate data from the literature that document the reduction of enteric neurons in IBD protocols [8][9][10]51]. In this study, after 7 days of acid injection, neuronal reduction was observed.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, recent evidence has indicated that colitis affects not only the intestinal mucosa but also the muscle layer and components of the ENS. Hence, gastrointestinal symptoms result from degenerative changes and a reduction in the number of enteric neurons and glial cells, sometimes induced by the P2X7 receptor[ 35 - 40 , 48 , 50 , 62 , 63 , 82 - 84 ]. However, little is known about the cellular signaling mechanisms responsible for the loss of enteric innervation in IBDs[ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, improving the understanding of the cellular and molecular basis of neuronal death can aid in the identification and development of specific therapeutic strategies[ 8 ]. However, studies on the mechanisms underlying the death of enteric neurons, especially the role of the P2X7 receptor as an inducer of the death of these neurons in inflammatory bowel diseases (IBDs), are still lacking[ 37 - 40 , 51 , 52 , 60 - 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, P2X7 receptors, which are shown in the present study to be expressed in the colonic epithelium, too (Figures 8–10), play a central role in a great spectrum of diseases. Consequently, inhibition of this ionotropic receptor may serve as approach for the treatment of inflammatory bowel diseases (Magalhães & Castelucci, 2021).…”
Section: Discussionmentioning
confidence: 99%